Intencionalumas – įminimo raktas ar esminė problema? - Lauruhin, Andrei (Problemos, 2004)
This investigation sets for itself the task of a critical reconsideration of the concept of intentionality in the descriptive psychology of Brentano and in the phenomenology of Husserl. The author focuses his attention on two problems: that of the ontological basis under an idea of “intentionale Inexistenz” of Brentano and that of the constitution of an individual thing in phenomenology of Husserl. The analysis discloses methodical and metaphysical assumptions of intentional analyses of Brentano (related to ontology of Aristotle and positivism) and of Husserl (related to the doctrine of Kant about “secretly functioning reason”).
Keywords: Intentional inexistence; intentional being; intentional constitution of perceptive experience; secretly functioning reason; ontological dimension of intentionality